(untitled) (Semiárida, 2018)
Bread wheat is the most important winter crop in the Pampean Semiarid Region, even under a scenario of high volatility in commodity prices. Other crops such as feed and malting barleys, oats, rye, durum wheat, canarygrass, triticale, rapeseed, safflower and flax can be grown alternatively in that season. The objective of this study was to evaluate the production performance of those alternative winter crops. Tests were conducted in the experimental field of the Agronomy Faculty of the Universidad Nacional de La Pampa (36°32’54” S; 64°18’16” W) on a Petrocalcic Paleoustoll soil. The experiment was run using a randomized complete block design with three replicates, and three dates of sowing were assayed: june 2, june 21 and august 14. Rain falling during the trial period was enough to meet the needs for all the crops, excepting for safflower in December and January. Bread wheat and the two types of barleys sown in the latest date, and triticale sown in the second date, showed the highest grain yield. Oats, feed and malting barleys, rye, durum and bread wheats, and safflower showed their highest grain yield when sown in the third date. The highest performance for canarygrass, triticale and flax was observed for the second date of sowing. The yield of the last ones was lower than that showed by the rest of crops assayed. Therefore, their choosing by the farmer would depend on a view of crop value chain, marketing niche and profitability. DOI: http://dx.doi.org/10.19137/semiarida.2016(01).19-24